An institutional ethnography inquiry of health care work in special education: a research protocol - Stella L. Ng; Rosamund Stooke; Sandra Regan; Kathryn Hibbert; Catherine Schryer; Shanon K Phelan; Lorelei Lingard (International Journal of Integrated Care, 2013)
Background: Special education for children with chronic health conditions or disabilities requires the integration of health care work with education. This phenomenon is an under-studied and challenging context for integrated care despite policies and protocols that outline work processes in this context. We are interested in an approach to inquiry that will allow us to address gaps in current literature and practices in integrated care, and move toward policy change. Study design and data collection methods: Institutional ethnography is an approach to inquiry that maps the actualities of what individuals do at an everyday local level, while examining this work activity in relation to the socio-political context. It has been used to change policy and local practice by highlighting disjunctures between policy and actuality. We are adopting institutional ethnography and its three common methods of data collection: document collection, interviews, and observations/shadowing. Informants to this inquiry are chosen from school-based teams, family-centered units, and constellations of clinical professionals. Methods of analysis: We are following work processes, verbally and visually mapping what is done and by whom. The mediating role of texts in work processes is also being mapped. It is important to note that work includes “unofficial” work, including the work of families and others who may not be officially assigned a work role in a policy or protocol. Conclusion: A primary outcome of this study will be the creation of maps that demonstrate the social organization of work processes occurring in the health care-special education interface. These maps will make invisible work visible, highlight disjunctures between policy and practice, and identify opportunities for change. They may be useful for educational purposes, providing an orientation to the complex terrain of integrated care to professionals and families.